2017
DOI: 10.1158/1078-0432.ccr-16-0414
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of MicroRNA-644a Promotes Esophageal Squamous Cell Carcinoma Aggressiveness and Stem Cell–like Phenotype via Dysregulation of PITX2

Abstract: Purpose: We previously reported the oncogenic role of pairedlike homeodomain 2 (PITX2) in esophageal squamous cell carcinoma (ESCC). In this study, we aimed to identify the miRNA regulators of PITX2 and the mechanism underlying the pathogenesis of ESCC.Experimental Design: Using miRNA profiling and bioinformatics analyses, we identified miR-644a as a negative mediator of PITX2 in ESCC. A series of in vivo and in vitro assays were performed to confirm the effect of miR-644a on PITX2-mediated ESCC malignancy.Res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 44 publications
2
45
0
Order By: Relevance
“…The metastasis-promoting function of Id1, MMP-1, integrin alpha6 and PITX2, for example, requires activation of the PI3K/AKT pathway [7, 2123]. Here, our results showed that p-AKT expression was increased in the highly invasive esophageal cancer sublines and was likely due to downregulation of PTEN.…”
Section: Discussionmentioning
confidence: 57%
“…The metastasis-promoting function of Id1, MMP-1, integrin alpha6 and PITX2, for example, requires activation of the PI3K/AKT pathway [7, 2123]. Here, our results showed that p-AKT expression was increased in the highly invasive esophageal cancer sublines and was likely due to downregulation of PTEN.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast a high PITX2 protein expression, suggestive of a low or unmethylated PITX2 gene, is found in colorectal cancer where the WNT/β-Catenin is predominantly activated due to APC mutations [53]. The same has been demonstrated in other tumors with an aberrant WNT/ß-catenin pathway like esophageal squamous cell cancer [54, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies against TRPM7 (1:200 dilutions, Abcam) were used in this study. Detailed procedures of IHC were as described previously (15). The intensity of staining in tumor cells was scored by two pathologists independently.…”
Section: Clinical Patient Cohort and Tissue Specimensmentioning
confidence: 99%